Study of Impact of the Coir Geo-Textile Usage on the Unpaved Roads (International Journal of Innovative Research in Engineering & Management, 2022)
Transportation infrastructure development  is crucial to a country's overall growth. Roads are one of the  most essential routes of transportation in the world, and they  play a crucial part in a country’s economic and social  development. Unpaved roads are typically utilised for low  traffic flow and serve as access roads; they are also known as  village roads. Unpaved roads serve a critical role in the rural  region economy and the resource sectors of agricultural and  resource-rich countries. a method is required that either  removes the requirement for good-quality aggregate or needs  the use of only a small amount of the such material while still  providing adequate road performance. Geosynthetics have  been utilised to improve unpaved roads on basis of soft  subgrades and to lengthen their service life. By adding  reinforcement, the aggregate layer thickness required for a  given traffic volume can be reduced, or the traffic volume  can be raised for a given aggregate layer thickness. Due to its  high lignin concentration, coir fibre is robust and degrades  slowly when compared to other natural fibres (Rao and  Balan, 2000). When embedded in the fill material, coir  geotextile creates good interface friction with granular fill,  which can cause tensile stress in the reinforcement.
Keywords: Coir Geo-Textile; Unpaved Roads; Coir fibre; Geotextiles